2017
DOI: 10.1126/sciadv.1601556
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles that do not adhere to mucus provide uniform and long-lasting drug delivery to airways following inhalation

Abstract: Debunking the mucoadhesion myth: Nonsticky particles for enhanced pulmonary drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(188 citation statements)
references
References 72 publications
8
179
1
Order By: Relevance
“…We note similar sample mixing and preparation techniques have been employed by other researchers studying nanoparticle transport in mucus [17,24]. Furthermore, previous studies from our group have confirmed that mucus samples subjected to these manipulations retain their expected bulk rheological properties and recapitulate ex vivo the in vivo barrier properties of mucus gels to nanoparticles [35,37,48,49]. After the particles were introduced into the sputum, the slide was sealed with a glass coverslip and then incubated at room temperature for 1–2 h to prevent advection during imaging.…”
Section: Methodssupporting
confidence: 64%
“…We note similar sample mixing and preparation techniques have been employed by other researchers studying nanoparticle transport in mucus [17,24]. Furthermore, previous studies from our group have confirmed that mucus samples subjected to these manipulations retain their expected bulk rheological properties and recapitulate ex vivo the in vivo barrier properties of mucus gels to nanoparticles [35,37,48,49]. After the particles were introduced into the sputum, the slide was sealed with a glass coverslip and then incubated at room temperature for 1–2 h to prevent advection during imaging.…”
Section: Methodssupporting
confidence: 64%
“…The advantages of these materials reside primarily in their size (at least one dimension should be at the nanometer level), since many biological systems such as viruses and proteins are nano-sized (25). Nanoparticles can be administered via sub-cutaneous and intramuscular injections, or can be delivered through the mucosal sites (oral and intranasal), and penetrate capillaries as well as mucosal surfaces (26,27). Recent progresses have allowed the preparation of nanoparticles with unique physicochemical properties.…”
Section: Nanoparticles An Alternative Approach To Conventional Vaccinesmentioning
confidence: 99%
“…These assays do not provide quantitative measurements of diffusion parameters, but nonetheless serve as a valuable bridge between in vitro studies and translation to the clinic. 47,52,88,89 …”
Section: Size-dependent Filtrationmentioning
confidence: 99%
“…51 Second, high-density surface-grafted PEG forms a brush that physically resists the adsorption of gel components, 153 while the low PEG molecular weight precludes adhesion to gel components due to chain entanglement. 51 Neither of these reasons is gel-specific, which explains why PEGylation seems to be fairly universally applicable to promoting diffusion in biological hydrogels: PEGylated particles effectively penetrate many types of mucus, 5153,89,154,155 biofilms, 44 and ECM. 47,156,157 In addition, recently Maisel et al (2016) recently showed that PEG molecular weights as high as 40 kDa can be used for mucus penetration, with higher molecular weights requiring extremely high PEGylation density to reduce entanglements.…”
Section: Selective Transport Of Objects On the Order Of Mesh Sizementioning
confidence: 99%